Transcriptional Profile of Diuron-Induced Toxicity on the Urinary Bladder of Male Wistar Rats to Inform Mode of Action - Ihlaseh, Shadia M. [UNESP]; Bailey, Kathryn A.; Hester, Susan D.; Jones, Carlton; Ren, Hongzu; Cardoso, Ana Paula F. [UNESP]; Oliveira, Maria Luiza Cotrim Sartor de [UNESP]; Wolf, Douglas C.; Camargo, João Lauro Viana de [UNESP] (Oxford University Press, 2011)
Diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is a substituted urea herbicide that induces rat urinary bladder urothelial tumors at high dietary levels (2500 ppm). The specific mode of action and molecular alterations triggered by diuron, however, have not been clarified. The present study evaluated the dose-dependent effects of mucosal alterations and transcriptional changes in the urinary bladder of rats exposed to diuron. Six-week-old male Wistar rats were treated with 0, 60, 125, 1250, and 2500 ppm of diuron in the diet for 20 weeks. Histologic examination showed urothelial hyperplasia present in rats treated with either 1250 or 2500 ppm of diuron but not 60 or 125 ppm. Comprehensive gene expression analyses of urothelial cell RNA were conducted using Affymetrix microarrays. The numbers of differentially expressed transcripts between each treatment group and control increased with diuron dose. Based on similar histology and gene expression responses, the treatment groups were regrouped into a high-dose (1250 and 2500 ppm) and low-dose group (60 and 125 ppm). These data suggest that persistent exposure to high dietary concentrations of diuron induces oxidative stress, increases cellular metabolism, and enhances cell death that is associated with sustained urothelial hyperplasia.
Keywords: diuron; urinary bladder; carcinogenesis; gene expression profiling; microarray analysis